The Importance of mechanical behaviour in orthodontic archwires - Hazel Roger J.; West Victoir C. (Sciendo, 1986)
For many years it has been recognised that the mechanical behaviour of the archwire material plays a central role in orthodontic treatment. Burstone et al (1961) recognised this in their analyses of the forces obtained from cantilevers and springs. Waters and his co-workers (1970-1975) have extended these analyses to include more complex appliances. A consequence of these theoretical examinations was the recognition of the mechanical parameters which were most important in practice. It is the intention in this paper to describe these parameters and to present data, obtained by the authors and from the literature, to compare a number of different archwire materials.